Polarization Evolution of Gamma-Ray Burst Prompt Emission with Bulk Acceleration - Qian Zhong; Hong-Bang Liu; Kangfa Cheng; Zu-Ke Feng; Jiang-Chuan Tuo; Qian-Nan Mai; Jirong Mao; En-Wei Liang (The Astrophysical Journal)
During the prompt phase, Poynting-flux-dominated jets undergo acceleration accompanied by magnetic dissipation. By using an outward-propagating thin-shell model, where bulk Lorentz factors Γ increase with radius and the magnetic field strength decay is related to the acceleration and the energy conversion rate, this process can be investigated through time-resolved polarization analysis. Faster acceleration produces a greater flux, steeper light-curve growth followed by a sharper decline, and polarization degree decreases sharply. With a fixed acceleration index, lower energy conversion rates are associated with lower flux, shallower rises and declines in light curves, lower polarization degree, smoother decline for on-beam ( q = θ _v / θ _j < 1) emission, and sharper decline for off-beam ( q > 1) emission in polarization curves. Both jet acceleration and magnetic dissipation enhance the likelihood of polarization angle flips in observations with small viewing angles, while also leading to higher polarization degrees after the flip in observations with larger viewing angles. The joint analysis of light curves and polarization provides valuable insights into gamma-ray burst motion and energy conversion processes. Rapid decline in the light curve indicates fast acceleration and high energy conversion rates, while gradual light-curve decline coupled with polarization angle flips (for small viewing angles) or the higher polarization degree after flipping (for large viewing angles) suggests acceleration accompanied by magnetic dissipation. Otherwise, the jet is coasting or slowly accelerating at this time.